DEPRESSIVE SYMPTOMS AND SELF-RATED POOR SLEEP QUALITY AMONG INDONESIAN OLDER ADULTS: A GENDER-STRATIFIED CROSS-SECTIONAL STUDY - Nopryan Ekadinata; Nur Fithriyanti Imamah; Rizka Dwi Pramesthi; Ines Zuyyina Zahra; Nadia Vitta Yulianti (Universitas Kusuma Husada Surakarta, 2026)
Background: Depressive symptoms and sleep disturbances are major challenges in healthy aging. A previous study highlighted the bidirectional consequences of depressive symptoms and sleep disturbances in older adults. However, gender differences in this association remain unclear. The study aimed to examine the association between depressive symptoms and self-rated poor sleep quality based on gender in older Indonesian adults.Methods: A cross-sectional study was conducted using door-to-door interviews with total sampling in a sub-village in Indonesia. The study included 121 older adults from one sub-village. Depressive symptoms were measured using the Geriatric Depression Scale (GDS). Sleep disturbance was assessed using a self-rated measure of overall sleep quality. Pearson’s chi-square and crude logistic regression by gender were utilized to infer the significant association.Results: The prevalence of depressive symptoms and sleep disturbances was 19% and 15.7%, respectively. Older women experience more sleep disturbances. Pearson chi-squared analysis resulted in the significant effects of depressive symptoms and sleep disturbance in older men only. Moreover, higher depressive symptoms corresponded to a higher probability of sleep disturbance in the general population (OR=3.135, p<0.05).Conclusion: The study confirms previous findings that underline the negative effects of depressive symptoms on sleep in older adults. The current study’s results can be used by health professionals to tailor specific programs to reduce depressive symptoms and improve sleep quality in older adults.